(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2020)
The method of visual object tracking intended for the application on multispectral video sequences is considered. Introduction. The possible techniques of multispectral information fusion for visual object tracking are considered and the use of feature based fusion approach is justified. The tracker is suggested to be implemented using the discriminative correlation filters (DCF), since this approach is known to provide the compromise in terms of tracking quality and speed. Theoretic results. The method for channel-independent discriminative correlation filter with spatial regularization calculation based on the use of alternating direction method of multipliers (ADMM) is proposed. The calculation of DCF filter and the object localization is suggested to be performed in special feature space, which employs the multichannel FHOG features and the features that are based on the backprojection of object weighted histogram. In particular, we propose to calculate the mentioned features for each channel of the respective frame of the multispectral video sequence with subsequent concatenation of obtained features into a single tensor, which forms the joint feature space. Conclusions. Using the VOT Challenge RGBT2019 subchallenge, it was shown that the implementation of the suggested method is competitive in terms of tracking robustness with more sophisticated approaches, including the ones that are based on the convolutional neural networks. During the experiments, it was additionally established that the increasing of context-background information gives slight tracking quality improvement compared to the basic method implementation, even when only FHOG features are used.